Modern Ideas about the Vaginal Microbiome and its Effect on Pregnancy Outcomes - Zh. E., Pakhomova; D. T., Kayumova; M. X., Karimova (European Journal of Life Safety and Stability (2660-9630), 2022)
Changing the vaginal microbiome is one of the leading problems contributing to adverse pregnancy outcomes. Violation of the vaginal microbiome in combination with the failure of the cervical barrier leads to the migration of bacteria into the amniotic cavity and the launch of pathological mechanisms leading to termination of pregnancy or premature birth. The article presents modern data on the role of the infectious factor in the genesis of miscarriage. The question of the ability of Lactobacillus iners to predispose to the development of pathological vaginal microflora is considered. Attention is paid to the main approaches to the prevention and treatment of dysbiotic disorders.